Wheel and Deal - Working Title & Co (gingko press, 2015)
Come along for the ride as Wheel & Deal – Carts on Wheels tours the broad range of mobile establishments roaming the world’s roads, parks, and greenways. Five chapters divide the traveling outfits based on how they are propelled, whether entirely human-powered, bicycle-driven, carried in cars, hauled by trucks, or ferried to and fro by public transportation. Projects featured include solar-powered ice cream carts, easily transportable folding homes for the homeless, an irreverent pedal-powered Popemobile, Chicago CTA’s Art on Track public transportation turned art gallery, and San Francisco’s much-loved Curry Up Now food truck. Readers will also find pop-up fashion shops, tiny self-contained offices, and an amazing variety of kitchens on wheels.
Adlib record nr. 530011051
Engels
boek